A review of the socioecological causes and consequences of cyanobacterial blooms in Lake Victoria - Olokotum, Mark; Mitroi, Veronica; Troussellier, Marc; Semyalo, Ronald; Bernard, Cécile; Montuelle, Bernard; Okello, William; Quiblier, Catherine; Humbert, Jean-François (Harmful algae, 2020)
Africa is experiencing high annual population growth in its major river basins. This growth has resulted in significant land use change and pollution pressures on the freshwater ecosystems. Among them, the Lake Victoria basin, with more than 42 million people, is a unique and vital resource that provides food and drinking water in East Africa. However, Lake Victoria (LV) has experienced a progressive eutrophication and substantial changes in the fish community leading to recurrent proliferation of water hyacinth and cyanobacteria. Based on an extensive literature review, we show that cyanobacterial biomasses and microcystin concentrations are higher in the bays and gulfs (B&Gs) than in the open lake (OL), with Microcystis and Dolichospermum as the dominant genera. These differences between the B&Gs and the OL are due to differences in their hydrological conditions and in the origins, type and quantities of nutrients. Using data from the literature, we describe the multiple ways in which the human population growth in the LV watershed is connected to the increasing occurrence of cyanobacterial blooms in the OL and B&Gs. We also described the consequences of cyanobacterial blooms on food resources and fishing and on direct water use and water supply of local populations, with their potential consequences on the human health. Finally, we discuss the actions that have been taken for the protection of LV. Although many projects have been implemented in the past years in order to improve the management of waste waters or to reduce deforestation and erosion, the huge challenge of the reduction of cyanobacterial blooms in LV by the control of eutrophication seems far from being achieved.